RANCANG BANGUN MESIN PEMARUT KELAPA TIPE SILINDER KAPASITAS 100 KG/JAM - Farhan Ilham Syair (2023)
Coconut is a fruit that has many benefits, especially in the food sector in Indonesia. To process coconut fruit into food, it is necessary to go through several processes, one of which is the shrinking of fruit flesh. The previous shredding process was carried out by bringing the coconut closer to the grated knife that rotated at high speed. This method takes a relatively long time and the safety of the hands used is not guaranteed. Therefore, the purpose of this study is to obtain safety for operators and increase production capacity of coconut grate machines. To find out this, a cylindrical type coconut shredder machine with enlarged dimensions and the addition of presses by increasing the number of revolutions per minute. The research method starts from planning, manufacturing processes, and testing tools. The machine is designed with dimensions of 22 x 20 x 90 cm and the average capacity produced is 239.9 kg / hour and has a work efficiency of 94.87%.